2021
DOI: 10.54565/jphcfum.1004433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyphosate Herbicide on Photosynthetic Pigments and Antioxidant Enzyme Activities in Corn (Zea mays L.) and Wheat (Triticum aestivum L.) Varieties

Abstract: ARTICLE INFOIn this study, it was determined that phytotoxic levels of glyphosate herbicide that will be banned in Europe may be at on wheat and corn plants. Biochemical responses due to the toxic effect of glyphosate at different concentrations were determined in corn (Zea mays L. cv. Ada 523) and wheat (Tritucum aestivum L. cv. Halis) varieties. For wheat and corn varieties, 4 different doses (0, 100, 500 and 1000 μM) of the herbicide were applied to 1-week-old and 15-day-old plants. Hydroponic medium was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It's also well known that a decrease in the chlorophyll content could be due to a decrease in the stomata aperture, aimed at limiting water losses by evaporation and by increased resistance to the entry of atmospheric CO 2 necessary for photosynthesis (Zhu et al, 2016;Enneb et al, 2020). Karabulut and Çanakcı (2021) showed that the oxidative stress created by glyphosate treatment caused decrease in chlorophyll (a+b). As well, Caglar et al (2011) analyzed the effects of the herbicide paraquat on chlorophyll content, observing that bread wheat varieties after paraquat herbicide treatment decreased chlorophyll content.…”
Section: Degradation Of Chlorophyll Contentmentioning
confidence: 99%
“…It's also well known that a decrease in the chlorophyll content could be due to a decrease in the stomata aperture, aimed at limiting water losses by evaporation and by increased resistance to the entry of atmospheric CO 2 necessary for photosynthesis (Zhu et al, 2016;Enneb et al, 2020). Karabulut and Çanakcı (2021) showed that the oxidative stress created by glyphosate treatment caused decrease in chlorophyll (a+b). As well, Caglar et al (2011) analyzed the effects of the herbicide paraquat on chlorophyll content, observing that bread wheat varieties after paraquat herbicide treatment decreased chlorophyll content.…”
Section: Degradation Of Chlorophyll Contentmentioning
confidence: 99%
“…Tulkova and Kabashnikova (2021) found that lipid peroxidation refers to a series of free radical reactions in unsaturated fatty acids and that an increase in lipid peroxidation activity under prolonged stress indicates a decline in the scavenging ability within plant cells. Karabulut and Canakcı (2021) analyzed the effects of the herbicide glyphosate in maize and wheat varieties and observed that plants produce antioxidant defense systems, including enzymatic and nonenzymatic methods, as a result of ROS accumulation. Thus, as the amount of ROS increases, the level of MDA begins to accumulate.…”
Section: Lipid Peroxidation Assaymentioning
confidence: 99%